USAHA ARANG BRIKET SOLUSI ATASI LIMBAH BAGLOG JAMUR TIRAM DI KOTA METRO - Etik Puji Handayani (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2019)
In the oyster mushroom cultivation, baglog only be used for one-time production of mushrooms. Therefore, the greater the effort mushroom In District of Metro East, the more waste was generated baglog, so the waste baglog need to recycled into a product that has a sale value before it becomes compost. Because the fungus baglog composition consisting of 80% sawdust, 10% rice bran, limestone 1.8%, 1.8% and 0.4% gypsum, then this waste can be used as Superkarbon. Initiation of business charcoal briquettes in District Metro East is an appropriate measure to overcome the impact of the environmental problems of the city. With carbonation method, milling, and clumping back will be obtained charcoal briquettes as a source of alternative energy. Keywords: organic waste, charcoal briquettes, alternative energy